2015
DOI: 10.1111/dsji.12074
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Conception Focused Curriculum: The Importance of Introducing Undergraduate Business Statistics Students to the “Real World”

Abstract: Continuing pressures are being placed on undergraduate business education to alter curriculum content and delivery. The anticipated product of these changes is a graduate that is capable of performing the higher order thinking skills needed to navigate a constantly changing, global business environment. This article describes the implementation of a conception‐focused curriculum in an undergraduate business statistics course that has guided students to become masters of the discipline through conception learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The number of concepts identified in this study is comparable to that identified in nursing (Brussow et al, 2019;Giddens et al, 2012); however, other disciplines have identified fewer core concepts (Rowland et al, 2011). This study identified concepts that are common across other disciplines, such as professional behavior, collaboration, communication, and leadership (Brussow et al, 2019;Burch, Burch, Heller, & Batchelor, 2015;Giddens et al, 2012), and those that are discipline-specific (e.g., food security, food systems, nutritional status, food properties).…”
Section: Discussionsupporting
confidence: 64%
“…The number of concepts identified in this study is comparable to that identified in nursing (Brussow et al, 2019;Giddens et al, 2012); however, other disciplines have identified fewer core concepts (Rowland et al, 2011). This study identified concepts that are common across other disciplines, such as professional behavior, collaboration, communication, and leadership (Brussow et al, 2019;Burch, Burch, Heller, & Batchelor, 2015;Giddens et al, 2012), and those that are discipline-specific (e.g., food security, food systems, nutritional status, food properties).…”
Section: Discussionsupporting
confidence: 64%
“…Many studies have documented students' difficulties with statistical concepts and misconceptions in reasoning about probabilities, sampling distributions, and inference (e.g., delMas, Garfield, Ooms, & Chance, 2007;Sotos, Vanhoof, Van den Noortgate, & Onghena, 2007). Other research provides recommendations for course-related improvements (e.g., Burch, Burch, & Heller, 2015;Chance, Wong, & Tintle, 2016;Garfield, Le, Zieffler, & Ben-Zvi, 2015;Levine & Stephan, 2011), and resources for curricula models, instruction, and assessment of statistical knowledge (e.g., Tishkovskaya & Lancaster, 2012). The literature also provides a rich variety of activities, simulations, and cases aimed at fostering student engagement in statistics classes (e.g., Dinov, Christou, & Sanchez, 2008;Kottemann & Salimian, 2008;Van der Rhee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by G. Burch, F. Burch, Heller, and Batchelor (2015), researchers explored the application of what they define as a conception-focused curriculum in an undergraduate business statistics course of 125 students. This curriculum guided student learning by using conception learning and real-world problem solving, encouraged students to acknowledge that most situations have more than one single correct solution, and motivated them to use analytical and practical thinking while drawing on a diverse knowledge base (Burch et al, 2015). The results of this study showed that students involved in the conception-focused curriculum perceived themselves as being higher order learners and global citizens (Burch et al, 2015).…”
Section: Related Literaturementioning
confidence: 99%
“…The study by Burch et al (2015), is just one of very few studies available that explore the concept of a real-world curriculum and students" perceived readiness for life after graduation. Because of this, there is an undeniable need for further research to provide students with useful knowledge and skills to prepare them to become successful employees in their specific career fields.…”
Section: Related Literaturementioning
confidence: 99%